2021
DOI: 10.1111/joca.12426
|View full text |Cite
|
Sign up to set email alerts
|

Why did (some) consumers buy toilet papers? A cross‐cultural examination of panic buying as a maladaptive coping response to COVID‐19

Abstract: The high uncertainty around the COVID‐19 pandemic elicited an unprecedented level of panic buying during the early months. Using the framework of stress and coping, the current study conceptualized and tested a theoretical model that predicts individuals' panic buying in two countries. A survey of US (n = 311) and Korean consumers (n = 347) revealed that negative emotions (loneliness and anxiety) contributed to panic buying, yet two important coping resources, resilience and social support, were effective in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 71 publications
(111 reference statements)
0
20
0
Order By: Relevance
“…It was indicated that both individualism and avoidance of uncertainty as an indication of national culture have a positive influence on panic buying (Messner & Payson, 2022). The research results determined that during the pandemic social support could be regarded as a source of coping as well as a source of increasing negative emotions (Im et al, 2022). It was also shown that emotional excitement generating a positive attitude towards campaigns relating to Covid-19 also translated into buying intentions (Chetioui&Lebdaoui, 2021).…”
Section: Literature Reviewmentioning
confidence: 97%
“…It was indicated that both individualism and avoidance of uncertainty as an indication of national culture have a positive influence on panic buying (Messner & Payson, 2022). The research results determined that during the pandemic social support could be regarded as a source of coping as well as a source of increasing negative emotions (Im et al, 2022). It was also shown that emotional excitement generating a positive attitude towards campaigns relating to Covid-19 also translated into buying intentions (Chetioui&Lebdaoui, 2021).…”
Section: Literature Reviewmentioning
confidence: 97%
“…The most investigated outcome is panic buying, which saw a marked increase in many countries. In a study of U.S. and Korean consumers, Im et al (2022) found that heightened anxiety led consumers in both countries to panic buying. In a survey of 1006 consumers in UAE, Sherman et al (2021) found anxiety to lead to panic buying.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, panic buying and hoarding behaviors of both physical products and digital content products have become a global phenomenon. Many existing literatures have studied the panic buying and hoarding behaviors of daily necessities, medicines and food during the period of COVID-19 [ [11] , [12] , [13] , [14] , [15] , [16] ]. Scholars believe that individual psychological factors [ [5] , [6] , [7] ] and social psychological factors are the main factors triggering people panic buying and hoarding food during the epidemic [ [8] , [9] , [10] ].…”
Section: Introductionmentioning
confidence: 99%